Challenges and Solutions in Evaluation Technical Assistance During Design and Early Implementation. (February 2022) - Gothro, Andrew; Hanno, Elías S.; Bradley, M. C.
This case study discusses two federal grant initiatives and the evaluation technical assistance (ETA) provided to the grantees. One program is a multiphase program funded by the Children's Bureau (CB) within the U.S. Department of Health and Human Services, Administration for Children and Families. The program funded communities interested in preventing homelessness among youth and young adults with child welfare histories. The funder, grantees, and ETA provider call it Youth At-Risk of Homelessness (YARH). Six federal agencies—the U.S. Departments of Education, Health and Human Services, and Labor, the Corporation for National and Community Service, and the Institute for Museum and Library Services—supported the second initiative known as Performance Partnership Pilots for Disconnected Youth (P3). We discuss the programs together as they share common features including a focus on building evidence, a focus on disconnected youth, use of liaisons to work with grantees who are developing interventions and planning or conducting evaluations at the same time, and having the same liaisons provide ETA to both the grantee/service providing group and the local evaluator. The article discusses (1) the grant programs, (2) details about ETA including its funding and provision, (3) details about the success and utilization of ETA, (4) benefits of ETA, and (5) balancing program or initiative requirements and evaluation needs and concludes with (6) thoughts on how to make ETA successful.